Work Ethic and Quality of Human Resources (HR) Affecting Police Performance at Polres Aceh Barat - Suriadi, Mimin; Mus, Khurial Tartati (Lembaga Riset Mutiara Akbar (LARISMA), 2023)
This research was conducted with the aim of finding out whether work ethic and human resource quality influence police performance at the West Aceh Police. Of the 440 existing populations, after calculations were carried out using the Slovin formula to determine the number of samples, 82 respondents were used as samples in this research. The entire sample was asked questions by distributing questionnaires and from distributing the questionnaires, the research results were obtained, namely: Based on the results of the t test (partial test) for variable X1, the sig value is 0.000 < 0.05. So in this case it means that variable X1 (Work Ethic) has a positive and significant influence on variable Y (Employee Performance). Meanwhile, for the variable X2, the sig value obtained is 0.058>0.05. So in this case it means that variable X2 (Quality of Human Resources) has no effect on variable Y (Employee Performance). Based on the results of the F ANOVA test (simultaneous test), variables X1 and X2 obtained a sig value of 0.000<0.05. So in this case it means that variables X1 and X2 simultaneously (together) have a positive and significant influence on variable Y. So the conclusion is that the hypothesis has been answered, namely that Work Ethic and Human Resource Quality have a positive and significant influence on Police Performance at the Pores Aceh Barat